Analysis of delayed core biopsy results during COVID-19 pandemic: the experience of a single public center - Ferrari, Marina Ávila; Ronsoni, Nadhine Feltrin; Ozol de Ávila, Gustavo Alberto; Cechella, Paula; Freitas, Adriana; Heinzen, Rebeca (Mastology, 2025)
To observe and analyze the waiting time for breast biopsy and the impact of this time on the early diagnosis of breast cancer in Santa Catarina. Methods: Observational cohort study. Data collection was performed through direct observation with the application of a questionnaire and subsequent quantitative analysis. A convenience sample was used, in which data were computed through a questionnaire administered to patients in cases where a breast biopsy with a thick needle was requested due to the existence of a suspicious lesion in the physical examination or in imaging examinations requested as breast cancer screening. Data from the collection instrument were extracted through direct interviews with patients in the office and completion of a questionnaire, after their correct guidance and signing of an informed consent form. The percentage of malignant versus benign lesions and the pain scale during core biopsy were evaluated. Results: The questionnaire was submitted to 71 women who attended the mastology outpatient clinic at the Hospital Regional de São José – Dr. Homero de Miranda Gomes (HRSJ-HMG) between October 2021 and May 2022. Of these, 7 did not undergo breast biopsy due to the lesion not being identified, 39.1% resulted in malignant neoplasia and 60.9% in benign lesion. Regarding the assessment of pain during core biopsy, 57.8% experienced mild or no pain, 21.8% moderate pain and 10.9% severe pain.